Globalization the external pressures - paul kirkbride, (JOHN WILEY & SONS, LTD)
Since 1959 Ashridge has earned the reputation of being one of the world’s leading business schools. Through all our activities, from executive education and post-graduate qualification programmes to research and consulting, we combine leading-edge thinking with a strong practical focus. We believe learning must be involving, challenging and above all real, so that it does make a significant difference when applied in the workplace. To this end we have reinforced and built upon the philosophy of our founders: that business needs to inform and reflect the environment in which it operates. Our work with clients and business school partners from all parts of the world endorses this still further. We know globalization is not an isolated subject, as it integrates with all organizational activities and as such creates fascinating business and development opportunities. Our faculty’s expertise in globalization has developed from research, observation, hands-on experience and passion for the subject. We are therefore delighted that our faculty members are able to share their learning and insights more widely by contributing chapters to two complementary books published by John Wiley & Sons. xii P R E F A C E ............................................................................ I hope you find these two books, Globalization: The Internal Dynamic and Globalization: The External Pressures help you address your own particular issues and I would be pleased to hear your thoughts and comments on Ashridge’s approach to globalization.Since 1959 Ashridge has earned the reputation of being one of the world’s leading business schools. Through all our activities, from executive education and post-graduate qualification programmes to research and consulting, we combine leading-edge thinking with a strong practical focus. We believe learning must be involving, challenging and above all real, so that it does make a significant difference when applied in the workplace. To this end we have reinforced and built upon the philosophy of our founders: that business needs to inform and reflect the environment in which it operates. Our work with clients and business school partners from all parts of the world endorses this still further. We know globalization is not an isolated subject, as it integrates with all organizational activities and as such creates fascinating business and development opportunities. Our faculty’s expertise in globalization has developed from research, observation, hands-on experience and passion for the subject. We are therefore delighted that our faculty members are able to share their learning and insights more widely by contributing chapters to two complementary books published by John Wiley & Sons. xii P R E F A C E ............................................................................ I hope you find these two books, Globalization: The Internal Dynamic and Globalization: The External Pressures help you address your own particular issues and I would be pleased to hear your thoughts and comments on Ashridge’s approach to globalization.Since 1959 Ashridge has earned the reputation of being one of the world’s leading business schools. Through all our activities, from executive education and post-graduate qualification programmes to research and consulting, we combine leading-edge thinking with a strong practical focus. We believe learning must be involving, challenging and above all real, so that it does make a significant difference when applied in the workplace. To this end we have reinforced and built upon the philosophy of our founders: that business needs to inform and reflect the environment in which it operates. Our work with clients and business school partners from all parts of the world endorses this still further. We know globalization is not an isolated subject, as it integrates with all organizational activities and as such creates fascinating business and development opportunities. Our faculty’s expertise in globalization has developed from research, observation, hands-on experience and passion for the subject. We are therefore delighted that our faculty members are able to share their learning and insights more widely by contributing chapters to two complementary books published by John Wiley & Sons. xii P R E F A C E ............................................................................ I hope you find these two books, Globalization: The Internal Dynamic and Globalization: The External Pressures help you address your own particular issues and I would be pleased to hear your thoughts and comments on Ashridge’s approach to globalization.